75.3k views
2 votes
4X-5y=13
6x +2y =48

Elimination

1 Answer

2 votes

Answer:

The answer to your question is: (7, 3)

Explanation:

Equations

4x - 5y = 13 (I) 1.- Assign numbers to each equation

6x + 2y = 48 (II)

2.- Multiply (I) by 3 and (II) by -2

12x - 15y = 39 (I)'

-12x - 4y = -96 (II)'

3.- Sum the equations

0 - 19y = -57

4.- Find y

y = -57/-19

y = 3

5.- Find x

4x - 5(3) = 13 Substitution

4x - 15 = 13 Simplifying

4x = 13 + 15

4x = 28

x = 28/4

x = 7

Result

(7, 3)

User Pilouk
by
5.3k points